SWEET Transporters and the Potential Functions of These Sequences in Tea (Camellia sinensis) - Jiang, Lan; Song, Cheng; Zhu, Xi; Yang, Jianke (Frontiers in Genetics, 2021)
The tea (Camellia sinensis) is an important economic beverage crop. Its flowers and leaves could be used as health care tea for its medicinal value. SWEET proteins were recently identified in plants as sugar transporters, which participate in diverse physiological processes, including pathogen nutrition, seed filling, nectar secretion, and phloem loading. Although SWEET genes have been characterized and identified in model plants, such as Arabidopsis thaliana and Oryza sativa, very little knowledge of these genes in C. sinensis. In this study, 28 CsSWEETs were identified in C. sinensis and further phylogenetically divided into four subfamilies with A. thaliana. These identified CsSWEETs contained seven transmembrane-helixes (TMHs) which were generated by an ancestral three-TMHs unit with an internal duplication experience. Microsynteny analysis revealed that the large-scale duplication events were the main driving forces for members from CsSWEET family expansion in C. sinensis. The expression profiles of the 28 CsSWEETs revealed that some genes were highly expressed in reproductive tissues. Among them, CsSWEET1a might play crucial roles in the efflux of sucrose, CsSWEET17b could control fructose content as a hexose transporter in C. sinensis. Remarkably, CsSWEET12 and CsSWEET17c were specifically expressed in flowers, indicating that these two genes might be involved in the sugars transport during flower development. The expression patterns of all CsSWEETs were differentially regulated under cold and drought treatments. This work provided a systematic understanding of the members from the CsSWEET gene family, which would be helpful for further functional studies of CsSWEETs in C. sinensis.